Diversification et fragmentation du financement public du développement: Rendre moins opaque et rationaliser la structure éclatée des financements du développement - Alain Le Roy; Jean-Michel Sévérino (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
– The fragmentation of public financing flows for developing countries appears to be an essential characteristic of the international financial architecture. This document explores the reasons for the proliferation of various institutions and funds and analyses its consequences in terms of efficiency, which are not all positive. After listing the various initiatives intended to reduce the harmful effects of the fragmentation of funding, such as the reduction in the number of funds, the search for greater transparency, a reform of multilateral institutions, the coordination of donors, it proposes the creation of a group of analysis, sharing, construction of common thought, fed by «scientific» information and in-depth comparative evaluation, which would bring together contributors and recipients. The possible locations of this instance are discussed.
Keywords: 330